THE EFFECT OF THE ADDITION OF CARRAGEENANON THE FISH NUGGET JAMBAL SIAM (Pangasius hypophthalmus) - Sanjaya, Boy; Sari, N Ira; Loekman, Suardi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The study was aimed to determine the effect of the addition of carrageenan on the quality of fish nuggets jambal siam (Pangasius hypophthalmus), assessed by using the organoleptic and chemical analyses. The method used was experimental with a completely randomized design (CRD) consisted of 4 levels of the treatment, namely, A0 (nuggets without the addition of carrageenan) as a control, treatment A1 (nugget with the addition of carrageenan 0.5%), treatment A2 (nugget with the addition of 1%), and treatment A3 (nugget with the addition of carrageenan 1.5%). The results showed that the addition of carrageenan 0.5% (A1) was the best treatment, indicated by the organoleptic characteristic neat appearance intact golden yellow, aroma slight smell of fish, a little flavor of the fish and savory, chewy texture compact and solid. It contained water 56.21% and protein 19.60%.Keywords : Nugget, Carrageenan, Fish jambal siam